Working Capital Management in Indonesia: An Analysis on Over-investment and Under-investment Firms - Rahmat Heru Setianto; Adinda Pratiwi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
This study aims to examine the existence of excess working capital in Indonesian firms and its effect on the firms’ performance and risk. The sample includes 425 firm-year observations of Indonesian manufacturing firms for the period 2010 – 2014. To account for the potential asymmetric relation between excess Net Working Capital (NWC) and firm performance, an asymmetric regression model is employed, allowing the slope coefficient of the excess NWC to be different for positive and negative excess NWC. The results indicate (i) the existence of an optimal level of working capital, (ii) higher excess working capital leads to lower performance and risk, (iii) additional investment in working capital reduces firms’ performance for those with positive excess working capital. It is also documented that (iv) additional investment in working capital reduces firms’ risk for those that have working capital deficiencies. The findings have important implications for corporate managers in determining the optimal level of working capital.